Densitas, Nilai Slump, Dan Kuat Tekan Beton OPC Dan OPC POFA Dengan Campuran Air Gambut Terpapar Di Lingkungan Gambut - Fadillah, M Lucky; Ismeddiyanto, Ismeddiyanto; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This research study aimed to test the density of fresh concrete, slump value and compressive strength of concrete using OPC cement and concrete with composition of 90%OPC+10%POFA (palm oil fuel ash). That concretes mixed with peat water. pH of peat water used ranges from 3.0 to 4.0. These specimens are cast in situ. Direct specimen exposed and soaked for 28 days in the peat canal. OPC concrete that mixed with peat water generate density values were small. An increase in the value of the slump of OPC concrete mixed with peat water compared to the controling OPC. As for concrete of 90%OPC+10%POFA slump value decreases. Compressive strength of OPC concrete and concrete of 90%OPC+10%POFA were soaked for 28 days in the peat showed relatively similar results compared to the normal condition.Keywords: OPC, palm oil fuel ash (POFA), peat water, peat area